Pelatihan Dasar-Dasar Penggunaan dan Keamanan Akun Gmail Bagi Ibu -Ibu PKK Desa Jompo Kulon - Davy Irsyad Tulloh; Lughri Wijaya Pamungkas; Nibras Asykar Zen; Ma’ruf Amrulloh; Muhammad Rafli Valdrian (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Advances in information technology increasingly require communities to adapt to digital communication tools, particularly email, which functions as a key digital identity for account registration, information exchange, and online transactions. Despite its importance, digital literacy remains limited among the general public, especially rural housewives, many of whom lack awareness of the need for email accounts, have limited operational skills, and are vulnerable to cyber risks such as phishing and data theft. To address this issue, a workshop entitled “Fundamentals of Using Gmail and Account Security” was conducted for the PKK women’s group in Jompo Kulon Village to improve basic digital skills and promote safe online practices. The program aimed to introduce the functions and benefits of email, assist participants in independently creating Gmail accounts, provide knowledge on securing accounts through two-factor authentication, and train participants to send and receive emails. The workshop was delivered through an interactive face-to-face approach combining short presentations and hands-on practice using participants’ mobile devices. Initial sessions explained email as a digital identity, followed by guided account creation and security setup. The final session focused on practicing email communication to reinforce understanding. The results showed high participant engagement, with most participants successfully creating Gmail accounts, understanding essential digital security concepts, and demonstrating basic email usage skills. Overall, the activity increased awareness of personal data protection and is expected to serve as an initial step in strengthening digital literacy among women, enabling them to better adapt to ongoing technological developments.